Aggregation of Streptococcus sanguis by a neuraminidase-sensitive component of serum and crevicular fluid. - Morris, E J (1983)
A number of strains of Streptococcus sanguis were found to aggregate in nonimmune serum and in crevicular fluid. All strains which aggregated in serum also aggregated in saliva, but some strains which aggregated in saliva did not aggregate in serum. Aggregation was destroyed by treatment of serum or crevicular fluid with neuraminidase and was inhibited by gangliosides. Treatment of serum with proteases reduced aggregating activity. Adsorption of serum to hydroxyapatite did not reduce the aggregating activity. The aggregating factor was partially purified by gel filtration and polyacrylamide gel electrophoresis and was found to be an acidic glycoprotein with a molecular weight of greater than 200,000, comprised of subunits with molecular weights of approximately 100,000. It did not appear to be an immunoglobulin and could not be identified with any other serum component tested. The possible role of the aggregating factor in providing nonimmune protection against colonization of S. sanguis in the gingival crevice and blood is discussed.